A study on mobile money and retail banking services in Kumasi Metropolis. - Obimpeh, Henry Agyei (2017)
A thesis submitted to the Department of Economics, College of Humanities and Social Sciences, in partial fulfilment of the requirement for the award of Master of Science in Economics,